Peningkatan Kesadaran Hukum Mahasiswa melalui Forum Diskusi Kritis terhadap RKUHAP di Kota Makassar: Improving Student Legal Awareness through a Critical Discussion Forum on the RKUHAP in Makassar City - Supratman, Andi; Herman, Herman; Muhtar, Muhtar; Khaer, Nurharsya; Randiawan, Randiawan (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The reform of Indonesia's criminal procedure law, as outlined in the Draft Criminal Procedure Code (RKUHAP), is set to take effect in January 2026 and has sparked mixed reactions among academics, legal practitioners, and civil society. This discussion was held as a moral calling and a form of academic protest against several articles in the RKUHAP that are perceived as granting excessive power to law enforcement authorities. The primary objective of this activity was to provide a more comprehensive understanding to students and student organizations from Universitas Negeri Makassar and Universitas Hasanuddin about the dynamics of criminal law reform in Indonesia, both from theoretical perspectives and practical experiences. The method employed was an open forum, consisting of two main sessions: one featuring conceptual insights delivered by academic lecturers, and the other analyzing real-life legal cases presented by representatives from the Legal Aid Institute (LBH) Makassar. The event took place in the courtyard of the BU Building at Universitas Negeri Makassar, with active participation from students across different faculties and organizations. The outcome showed that participants gained a deeper and more complete understanding of how complex the criminal procedure reform really is. They could see both the potential for stronger human rights protection on one hand, and the risks of backsliding on due process principles on the other. Overall, this event made a significant contribution to shaping critical legal awareness among students as agents of change and to encouraging more youth involvement in advocating for legal reform in Indonesia.